SDSS IV MaNGA – sSFR profiles and the slow quenching of discs in green valley galaxies. Issue 3 (22nd March 2018) - Belfiore, Francesco; Maiolino, Roberto; Bundy, Kevin; Masters, Karen; Bershady, Matthew; Oyarzún, Grecco A; Lin, Lihwai; Cano-Diaz, Mariana; Wake, David; Spindler, Ashley; Thomas, Daniel; Brownstein, Joel R; et al.
Abstract: We study radial profiles in H α equivalent width and specific star formation rate (sSFR) derived from spatially resolved SDSS-IV MaNGA spectroscopy to gain insight on the physical mechanisms that suppress star formation and determine a galaxy's location in the SFR- M ⋆ diagram. Even within the star-forming 'main sequence', the measured sSFR decreases with stellar mass, in both an integrated and spatially resolved sense. Flat sSFR radial profiles are observed for log( M ⋆ /M⊙ ) < 10.5, while star-forming galaxies of higher mass show a significant decrease in sSFR in the central regions, a likely consequence of both larger bulges and an inside-out growth history. Our primary focus is the green valley, constituted by galaxies lying below the star formation main sequence, but not fully passive. In the green valley we find sSFR profiles that are suppressed with respect to star-forming galaxies of the same mass at all galactocentric distances out to 2 effective radii. The responsible quenching mechanism therefore appears to affect the entire galaxy, not simply an expanding central region. The majority of green valley galaxies of log( M ⋆ /M⊙ ) > 10.0 are classified spectroscopically as central low-ionization emission-line regions (cLIERs). Despite displaying a higher central stellar mass concentration, the sSFR suppression observed in cLIER galaxies is not simply due to the larger mass of the bulge. Drawing a comparison sample of star-forming galaxies with the same M ⋆ and $\rm Σ _{1\, kpc}$ (the mass surface density within 1 kpc), we show that a high $\rm Σ _{1\, kpc}$ is not a sufficient condition for determining central quiescence.